Gynecological problems of adolescent girls attending to rural tertiary care centre - Patil, Suman Shivanagouda; Mahanthshetty, Hemalatha; H. M., Supriya; M., Mahendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Adolescence is a transient and dynamic period between childhood and adulthood, characterised by several changes in the body and the child’s mind. The World Health Organization defines adolescents as young people aged 10-19 years, but changes may begin before and continue after this age group. Adolescents constitute over 21.4% of population in India. Adolescence is a period of enormous physical and psychological change for young girls. Hormonal events play a key role in this transition. One of the major physiological changes that take place in adolescent girls is the onset of menarche, which is often associated with problems of irregular menstruation, excessive bleeding and dysmenorrhea. The aim of this study was to determine the proportion of various gynecological problems among adolescent girls seeking care at a tertiary care centre, Kolar, Karnataka, India. Methods: A cross sectional study was conducted during March 2016 to March 2018 among all adolescent girls (10-19 years) with gynecological problems attending inpatient and outpatient Department of Obstetrics and Gynecology. A pre-tested semi-structured questionnaire was used to collect information regarding their socio-demographic characteristics, gynecological history, family history, obstetric history, documentation of general physical examination and other investigations. Data entered using Microsoft Excel and analysed using SPSS v20. Results: A total of 720 adolescent girls sought care for gynecological problems in the study period with more than 80% of the cases belonging to the age group between 15 and 19 years. Of the 720, 362 (49.8%) had some type of menstrual disorders. Of these 362 cases about 41 of them were a case of puberty menorrhagia (11.32%) and 89 cases were of dysmenorrhea (22.37%). Among 720 cases, 290 (40.2%) of them were diagnosed of teenage pregnancy; among which 34 of them were unwanted pregnancy. Other presentations include vaginal discharge, urinary tract infection, mass per abdomen, trauma to genital tract and turners syndrome (two cases). Conclusions: The study shows around half of the adolescent girls are having menstrual disorders. One third were teenage pregnancies with most of them been ‘wanted’. This alarming finding calls for strengthening of adolescent programme with targeted health education and behavioural change. Setting up a separate adolescent clinics is necessary for efficient management of menstrual disorders in adolescents.